Origin, activation, and targeted therapy of glioma-associated macrophages - Xu, Can; Xiao, Menglin; Li, Xiang; Xin, Lei; Song, Jia; Zhan, Qi; Wang, Changsheng; Zhang, Qisong; Yuan, Xiaoye; Tan, Yanli; Fang, Chuan (Frontiers in Immunology, 2022)
The glioma tumor microenvironment plays a crucial role in gliomas' development, occurrence, and treatment. Glioma-associated macrophages (GAMs) are the most widely infiltrated immune cells in the tumor microenvironment and the main cell population that exerts immune functions. GAMs typically originate from two cell types, brain-resident microglia（BRM） or bone marrow-derived monocytes（BMDM）, and depend on a variety of cytokines for recruitment and activation. GAMs mainly contain two functionally and morphologically distinct activation types: classically activated M1 macrophages and alternatively activated M2 macrophages, which exhibit antitumor/immunostimulatory and protumor/immunosuppressive effects, respectively. GAMs have been shown to affect multiple biological functions of gliomas, including promoting tumor growth and invasion, angiogenesis, energy metabolism, and treatment resistance. Both M1 and M2 macrophages are highly plastic and can polarize or interconvert under various regulatory factors. As the relationship between GAMs and gliomas has become more apparent, GAMs have long been one of the promising targets for glioma therapy, and many studies have made good progress. Here, we review the origin and activation of GAMs in gliomas and how they regulate tumor development and response to therapy, and current glioma therapeutic strategies targeting GAMs